Profile of soft skill and habits of mind prospective biology teacher - I Y N Hizqiyah; A Widodo; Riandi Riandi; S Sriyati (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Softskill and habits of mind is an ability that must be possessed by biology teacher candidates especially in solving problems. This study aims to describe the profile of softskill and habits of mind of biology teacher candidate of FKIP Pasundan University. This research used survey method with qualitative descriptive technique. The results of the research obtained information that there are 12 subjects are dislike by the students of Biology Education Program of Unpas University, thoose are: Genetics, Physiology and Entomology, Criptogamae Botany, Phanerogamae, Statistics, Nutrition Science, Animal Physiology, Sundanese Culture, Chemistry, and Physics for Biology. The ability of students thinking skill of Biology Education Study Program of FKIP Unpas in problem solving especicially in solvea problem as a whole has bad category.